Peningkatan Hasil Belajar PJOK Materi Permainan Bola Voli Peserta Didik melalui Model Discovery Learning di Kelas V SD Negeri 03 Payakumbuh Semester Ganjil T.P 2022/2023 - Marianto Marianto (Departement of Mathematics Education, 2022)
This study aims to see and analyze the increase in PJOK learning outcomes of students through the discovery learning model in Class V SDN 03 Payakumbuh odd semester TP 2022/2023.